2014
DOI: 10.1007/s40071-014-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of coral reef-associated zoanthids off Qeshm Island, northern Persian Gulf

Abstract: The Persian Gulf, a semi-enclosed sea in the subtropical northwest of the Indian Ocean, is noted for its unique biodiversity under its extreme ecological conditions. Despite high biodiversity levels, many groups of marine invertebrates in this area have remained uninvestigated. The order Zoantharia (zoanthids) is one of these taxonomically neglected groups. In this study, diversity of shallow water zoanthids off the Qeshm Island, the largest island in the Persian Gulf, was investigated for the first time. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The zoantharians found in this study were Zoanthus sansibaricus, Palythoa tuberculosa, Palythoa aff. mutuki (also reported in Noori Koupaei et al ., 2014), Palythoa mutuki and Neozoanthus sp. Iran.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The zoantharians found in this study were Zoanthus sansibaricus, Palythoa tuberculosa, Palythoa aff. mutuki (also reported in Noori Koupaei et al ., 2014), Palythoa mutuki and Neozoanthus sp. Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Previously three species of zoantharians were reported from Qeshm Island based on one mitochondrial marker, 16S rDNA (Noori Koupaei et al ., 2014). The present study clearly demonstrated the presence of five species groups in the islands located in the vicinity of the Strait of Hormuz, Persian Gulf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the low slope of the coast as well as being protected from sea turbulence and waves, the sedimentary areas are usually rich in organic matter (Mirzabagheri et al, 2018;Noori-Koupaei et al, 2014. Mudflats of Hormuz Island are located in the eastern and northeastern parts of the island (Bruthans et al, 2006) (Figure 11).…”
Section: Hara or Mangrove Forestsmentioning
confidence: 99%
“…Article 23.9.1.2 of the Code is fulfilled as the family-group name Sphenopidae Hertwig, 1882, is in current and widespread usage, as evidenced by the 30 publications by 99 different authors over the past 34 years using Sphenopidae as a valid name for the taxon it denotes (viz., Nagabhushanam and Jothinayagam 1982: 17; Ryland et al 2000: 191, 192; Ryland and Lancaster 2003: 407, 409, 415; Ryland and Lancaster 2004: 180; Ryland and Westphalen 2004: 411; Ryland et al 2004: 1195, 1197; Acosta et al 2005: 147–149, 151, 154, 160; Sinniger et al 2005: 1122, 1125, 1126; Daly et al 2007: 144; Sinniger et al 2008: 1254, 1256, 1257; Fautin and Daly 2009: 356; Del Mónaco et al 2010: 360; Reimer and Sinniger 2010: 251; Reimer et al 2010c: 606, 616; Swain 2010: 2592; Reimer et al 2011a: 983, 985, 987, 989, 991, 992; Cavallari et al 2012: 25; Longo et al 2012: [1]; Palmer et al 2012: 3880; Reimer et al 2012b: 43, 45, 47, 49; Rodríguez-Viera et al 2012: 32; Costello et al 2013: [2]; Fujii and Reimer 2013: 510, 516; Krishna and Gophane 2013: 210; Koupaei et al 2014: 64; Alencar et al 2015: 1113, 1114, 1121; Irei et al 2015: 1, 2, 4, 6, 14–16, 20; Qin et al 2015: 100; De la Cruz-Francisco et al 2016: 24; Fujii and Reimer 2016: 11, 12, 14, 17, 19, 20; Risi and Macdonald 2016: 113).…”
Section: Synonyms Of Epizoanthus Gray 1867 (Epizoanthidae) (I): Cortmentioning
confidence: 99%